ADAPTOGENESIS AND BIOLOGICAL POTENTIAL OF CATTLE ON СOMMERCIAL DAIRY FARM - Semenov, V.G.; Yelemesov, K.Ye.; Alentayev, A.S.; Tyurin, V.G.; Baimukanov, A.D. (Scientific Journal of Pedagogy and Economics, 2020)
The possibility of activating adaptive processes and organism resistance of cattle on commercial dairy farms under the influence of biological stimulants (polystim and PV-1) is proved. Biostimulants reduced the risk of gynecological disorders in cows: they reduced the retention time of placenta and subinvolution of uterus, reduced the endometritis and mastitis occurrence; increased reproductive function: shortened the time of the first estrus coming, increased the fertility, reduced the conception rate and duration of the service period, and improved the physicochemical composition of colostrum. The used biostimulants contributed to the increase in live weight of calves while increasing the relatively high level of assimilative processes associated with the fact that their forage energy was mainly spent on increasing body weight. At the same time, in calves not injected with biological preparations, it was mainly spent on providing homeothermia (i.e., maintaining constant body temperature), which was especially evident at low external temperatures. In calves raised in the conditions of intensive technology in winter, after the administration of dostim and polystim, the following indicators were significantly higher: the phagocytic activity of leukocytes by 5.4% - 6.4%, the lysozyme activity of plasma - by 3.0% - 6.2%, the blood serum bactericidal activity - by 7.1% - 9.5% and the content of immunoglobulins - by 2.5 mg/ml - 3.1 mg/ml. With the adaptive technology, the data of these indicators were higher: in winter period - by 5.2 - 6.4%, 3.1 - 6.2%, 6.0 - 8.7% and 4.7 - 5.7 mg/ml; and in spring-summer period - by 0.2 - 0.6%, 4.6 - 5.7%, 4.9 - 7.2% and 3.4 - 4.8 mg/ml (P<0.05-0.001), respectively.